Controlled Speaking Practices of Senior High School Students at SMA TA’MIRIYAH - Sudarmono (PT. Lembaga Penerbit Penelitian Nusantara, 2026)
This paper discussed the result of Controlled Speaking Practices of Senior Students at SMA. This teaching technique had a big contribution to improve accuracy and fluency in speaking. The study aimed to investigate the strengths and weaknesses of Controlled Speaking Practices and it was also to find whether Controlled Speaking Practices is effective in improving the speaking skill of senior students or not. The study took place at SMA TA’MIRIYAH Surabaya. The school carried out Controlled Speaking Practices in conversation class in the first grade of senior high school students. Qualitative descriptive approach and observation were applied in this study. The writer used recording and field notes as the techniques in conducting observation. The writer analyzed the strengths and weaknesses of controlled speaking practice which were according to three aspects: the result of practicing the task, how the teacher conducted the task, and the way students’ talk in the class. From the data analysis, Controlled Speaking Practices also can indicate that this is the right technique to improve the students’ speaking skill. The researcher concluded that Controlled Speaking Practices might be a tool of practice speaking English which can assist the students to achieve good speaking English.